A novel HLA‐A allele, A*74:23, identified in an individual from Costa Rica. Issue 6 (27th October 2014) - Arrieta‐Bolaños, E.; McWhinnie, A. J.; Madrigal‐Sánchez, J. J.; Calvo, L.; Salazar‐Sánchez, L.; Madrigal, J. A.; Marsh, S. G. E.; Shaw, B. E.
<x xml:space="preserve">Abstract</x> The new HLA‐A*74:23 allele differs from the closest allele A*74:01 by a nucleotide change in exon 3 at codon 97.